Universal access to drinking water: The role of aid - Robert Bain; Rolf Luyendijk; Jamie Bartram (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Financing and the role of aid within the water sector are poorly understood. We estimate the levels of spending achieved in developing countries during the Millennium Development Goals period to be US80 billion per year. Aid represented a substantial proportion of total sector financing in sub-Saharan Africa and Oceania (25 and 10 per cent, respectively) but less in other regions. Longitudinal analysis shows no detectable effect of volume of aid on progress. Importantly, we were unable to evaluate 'catalytic' aid. As the world approaches universal access to improved water, aid must increasingly focus on sustaining progress and assisting countries that still have sizable unserved populations.
Keywords: F35; O18; H41; L95; 330; water supply; foreign aid; Millennium Development Goals